2014
DOI: 10.1016/j.knosys.2013.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic exploration designs for graphical models using clustering with applications to petroleum exploration

Abstract: The paper considers the problem of optimal sequential design for graphical models. The joint probability model for all node variables is considered known. As data is collected, this probability model is updated. The sequential design problem entails a dynamic selection of nodes for data collection. The goal is to maximize utility, here defined via entropy or total profit. With a large number of nodes, the optimal solution to this selection problem is not tractable. Here, an approximation based on a subdivision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…When using the range of 5 cells, the proportion of neighboring facies type is lower as the sampling area has a lower overlap with the neighbor facies type in the concept models (see Figs. 4,5,6,7,8). Increasing the search range from 5 to 10 adds more spatial uncertainty, systematically increasing the entropy and reducing the prior EV of all deriving JDPs.…”
Section: Results Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…When using the range of 5 cells, the proportion of neighboring facies type is lower as the sampling area has a lower overlap with the neighbor facies type in the concept models (see Figs. 4,5,6,7,8). Increasing the search range from 5 to 10 adds more spatial uncertainty, systematically increasing the entropy and reducing the prior EV of all deriving JDPs.…”
Section: Results Analysismentioning
confidence: 99%
“…During the interactive process of creating the JPD, we observed that the maps from Figs. 4,5,6,7,8, and the marginal distributions, are good overall indicators of how well the JPD captures the experts' expectations considering the chosen parameters.…”
Section: Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…DEFINITION 6 (Multi-instance Graphical Clustering [17]): Assume that dynamic programming is set up for each cluster, given the current evidence. By considering a variation of (Eq.…”
Section: Clustering Strategies Of Multiple Clusters Updatementioning
confidence: 99%
“…Sequential optimization problems are typically solved using dynamic programming (Bellman, 1957;Puterman, 2005), but the 'curse of dimensionality' that is encountered in larger problems requires computational techniques for approximate solutions (Powell, 2011). Some of these methods have been deployed for solving sequential decision problems in applications with dependence, including models such as graphical models or Bayesian networks (BNs) (Krause and Guestrin, 2009;Brown and Smith, 2013;Martinelli et al, 2013a), Markov random fields (Bonneau et al, 2014;Martinelli and Eidsvik, 2014) and Gaussian processes (GPs) (Srinivas et al, 2010). In the rock hazard application, we compare some common heuristics for sequential information gathering.…”
Section: Introductionmentioning
confidence: 99%